Blood flow restricted and traditional resistance training performed to fatigue produce equal muscle hypertrophy. Issue 6 (21st January 2015) - Farup, J.; de Paoli, F.; Bjerg, K.; Riis, S.; Ringgard, S.; Vissing, K.
Abstract : This study investigated the hypertrophic potential of load‐matched blood‐flow restricted resistance training (BFR) vs free‐flow traditional resistance training (low‐load TRT) performed to fatigue. Ten healthy young subjects performed unilateral BFR and contralateral low‐load TRT elbow flexor dumbbell curl with 40% of one repetition maximum until volitional concentric failure 3 days per week for 6 weeks. Prior to and at 3 (post‐3) and 10 (post‐10) days post‐training, magnetic resonance imaging (MRI) was used to estimate elbow flexor muscle volume and muscle water content accumulation through training. Acute changes in muscle thickness following an early vs a late exercise bout were measured with ultrasound to determine muscle swelling during the immediate 0–48 h post‐exercise. Total work was threefold lower for BFR compared with low‐load TRT ( P < 0.001). Both BRF and low‐load TRT increased muscle volume by approximately 12% at post‐3 and post‐10 ( P < 0.01) with no changes in MRI‐determined water content. Training increased muscle thickness during the immediate 48 h post‐exercise ( P < 0.001) and to greater extent with BRF ( P < 0.05) in the early training phase. In conclusion, BFR and low‐load TRT, when performed to fatigue, produce equal muscle hypertrophy, which may partly rely on transient exercise‐induced increases in muscle water content.